Priority setting in research: user led mental health research. Issue 1 (December 2017) - Ghisoni, Marjorie; Wilson, Christine; Morgan, Karen; Edwards, Bethan; Simon, Natalie; Langley, Emma; Rees, Helen; Wells, Amanda; Tyson, Philip; Thomas, Phil; Meudell, Allen; Kitt, Frank; et al.
Plain English summary Involving people in health research is increasingly recognised as being important to make sure that research is focused more on the needs of people who use health services. At present, ideas about what should be researched most often comes from researchers and/or health professionals like doctors and nurses rather than people with a lived experience of mental illness. In this study, we will talk with this group of people from across Wales to explore what they think research into their health services should focus on. The findings from this work will help to influence the work of the National Centre for Mental Health Research Partnership Group; as well as` researchers and health professionals and others who concentrate on mental health research. The Research group is a partnership between people with a lived experience of mental ill health and professionals with an interest in mental ill health. The group plan to take forward the ideas that came from this research and some of the ideas have already been used to increase funding in the area of mental health research. Abstract Background This paper is the result of continued collaboration between members of the Service User and Carer Research Partnership, based in Wales and supported by the National Centre for Mental Health, Health and Care Research Wales, and Hafal. The aim of this study was to explore the research priorities of people with experience of mental health services which include people with a lived experience of mental ill health, their carers, and professionals. Method A nominal group technique was used to gather data. A one-day workshop 'Getting Involved in Research: Priority Setting' was held to gather the ideas and suggestions for research priorities from people who have experience of mental health services. Results Twenty-five participants attended the workshop. 5 were mental health professionals, 20 had a lived experience of mental ill health, (of which 3 were also carers). 11 were male and 14 were female. 120 research ideas were generated across 6 'Ideas Generating Workstations'. Participants took part in a 3 stage vote to narrow down the ideas to 2 main research priorities. Conclusion The two main research priority areas that were identified:1. 'Developing the knowledge of mental health issues amongst school-aged children' as a vehicle to overcome stigma and discrimination, and to support young people to manage their own mental health. 2. 'Developing education as a tool for recovery', for example by peer support. In addition, participants engaged in a notable discussion over the research priority: 'How are carers supported during the recovery of the person for whom they care?'